Factors influencing willingness to pay for conservation of deltaic mangrove forest resources in district of Kuching - Bon, Anna Sin Yii (Universiti Malaysia Sarawak, 2011)
This study is aimed at estimating the value of the conversation of the resources by determining the willingness to pay by the local communities for the conservation of the mangrove resources. Data for the study is collected from the local communities living near the mangrove forests and the WTP is obtained by using the contingency valuation technique.